FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN MEMILIH BELANJA DI PASAR BADUNG - Ida Ayu Trisna Wijayanthi; Fitra Satam (Warmadewa Management and Business Journal (WMBJ), 2022)
This research is a case study on Badung Market Consumers in Denpasar City. The purpose of this study is to determine: 1) the factors that influence consumer decisions in choosing Badung Market as a place to shop; 2) what are the most dominant factors that influence consumer decisions in choosing Badung Market as a place to shop. Data collection was taken from 100 respondents by distributing questionnaires. The sampling technique used is the Purposive Convinience Sampling model, where the respondents are people who are shopping at Badung Market. The data analysis technique used is Multiple Linear Regression Analysis. Based on the results of the study, it can be seen that: simultaneously cultural factors, social factors, personal factors and psychological factors have a positive and significant effect on consumer decisions in choosing Badung Market as a place to shop. while partially cultural factors, social factors and personal factors have a positive influence, while psychological factors have a negative effect. The factor that has the most dominant influence is the cultural factor, because it has a beta coefficient value of 0.959 compared to the coefficient value of social factors (x2) of 0.027, personal factors (x3) of 0.018, and psychological factors (x4) of 0.008.